Isolation of new neolignans and an unusual meroterpenoid from Piper cabagranum - de Oliveira, Celso R.; Ledvina, Zachary D.; Leonard, Michael D.; Odoh, Samuel O.; Dodson, Craig D.; Jeffrey, Christopher S. (Frontiers in Natural Products, 2024)
A novel meroterpenoid cabagranin D was isolated along with related neolignans cabagranis A-C from the leaves of Piper cabagranum (Costa Rica). Cabagranins A-C represent the first examples of 3,3'-neolignans isolated from the plant genus Piper, and the meroterpenoid cabagranin D displays an unprecedented ͗ Diels Alder conjugate of an unsubstituted phenylpropenone and α-phellandrene. Details of the full structural elucidation of these compounds and a discussion of their potential biosynthetic relationships are presented.This is a provisional file, not the final typeset article new series of dehydrodieugenol derived 3,3'-neolignans (cabagranins A-C; 1-3), which implicate the novel biosynthetic connections between cabagranin D (5) and the co-isolated neolignans (Figure 1). Herein, we report the isolation, structural, and stereochemical characterization of new meroterpenoid 5 and neolignans 1-3, natural products from Piper cabagranum (Costa Rica).Leaf samples of P. cabagranum were collected from La Selva Biological Station and Tirimbina Biological Reserve and verified (voucher # EJT3531) in March 2012. The leaves were oven dried (35-40 °C), and ground to a fine powder.The ground leaf material (1 g) was twice extracted with 400 mL of HPLC grade hexanes for 2 hours under mechanical agitation. The supernatants were pooled and evaporated under reduced pressure. Following, the spent plant material was twice extracted with HPLC grade (Fischer Scientific, Hampton, NH) acetone under the same conditions, and the supernatants were combined and evaporated under reduced pressure resulting in 200 mg of crude acetone extract and 100 mg of the hexanes extract. The crude acetone extract (180 mg) was dissolved in methanol (3 mL) and then purified via RP-HPLC (Poroshell C18, 21.2 mm x 150 mm,